Joshua - McConville, J. G. (The Two Horizons New Testament Commentary Ser, 2010)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- Abbreviations -- Introduction to Joshua (Gordon McConville) -- The Book -- The Audience of Joshua -- Dating and Historicity -- Reading Joshua as Scripture -- Joshua and Theology -- Commentary on Joshua (Gordon McConville) -- Theological Horizons of Joshua (Stephen Williams) -- Theology in the Book of Joshua -- The Question of the Land -- Possession and Loss -- The New Testament and the Land -- Back to the Land? -- The Question of Genocide -- The Grim Tale -- What and Why? -- Did God Really Say . . . ? -- Radical Accommodation -- Conclusion -- Idolatry -- At Stake -- Practices of the Nations -- The Practice of Israel -- A Matter of Life and Death -- Touching on Beauty -- Covenant -- Behind the Covenant -- Covenant and Privilege -- Covenant and Law -- Conclusion -- God of Miracle and Mystery -- Something Rich and Strange -- Approaching the Miraculous -- What Exactly Are We Told? -- The Scientific Question -- The Half-Seen World -- Joshua and Biblical Theology (Gordon McConville) -- Introduction -- Key Themes of the Book of Joshua -- Joshua and Genesis -- Joshua and Exodus -- Joshua and Leviticus -- Joshua and Numbers -- Joshua and Deuteronomy -- Joshua and JudgesâKings -- Conclusion -- Joshua in Biblical Theology -- The Problem of Evil and Violence -- JoshuaâKings: Chaos, History, and Violence -- Joshua, Chaos, and History in the Rest of the Old Testament -- Conclusion -- A Response to Gordon McConville (Stephen Williams) -- Reading Joshua Today (Stephen Williams) -- The Question of History -- The God of Joshua -- God as Personal -- God of Power -- The Character of God -- Divine Lordship -- A Response to Stephen Williams (Gordon McConville) -- Bibliography -- Author Index -- Scripture Index